Symbolic Meaning of Drama â€œPerlawanan Diponegoroâ€ - Sahid, Nur; Susantina, Sukatmi; Septiawan, Nicko (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2016)
Study on Drama entitled â€œPerlawanan Diponegoroâ€ or â€œDiponegoro Insurrectionâ€ by Lephen Purwanto is aiming at deeply digging the semiotic meanings attached to it. This study employed Keir Elamâ€™s theatrical semiotics as the approach, while Krippendorfâ€™s content analysis was implemented as the method of study. Citing from Krippendorf, content analysis is a method that is particularly develop to study symbolical phenomena with a major purpose that is to dig and reveal other examined phenomena, comprising content, meaning, and essential element of a literary work.